SUMBER-SUMBER RESILIENSI PADA REMAJA AKHIR YANG MENGALAMI KEKERASAN DARI ORANGTUA PADA MASA KANAK-KANAK - Devina Calista; Garvin Garvin (Psibernetika, 2018)
Child abuse by parents is common in households. The impact of violence on children will bring short-term effects and long-term effects that can be attributed to their various emotional, behavioral and social problems in the future; especially in late adolescence that will enter adulthood. Resilience factors increase the likelihood that adolescents who are victims of childhood violence recover from their past experiences, become more powerful individuals and have a better life. The purpose of this study was to determine the source of resilience in late adolescents who experienced violence from parents in their childhood. This research uses qualitative research methods with in-depth interviews as a method of data collection. The result shows that the three research participants have the aspects of "I Have", "I Am", and "I Can"; a participant has "I Can" aspects as a source of resilience, and one other subject has no source of resilience. The study concluded that parental affection and acceptance of the past experience have role to the three sources of resilience (I Have, I Am, and I Can) Keyword : Resilience, adolescence, violence, parents